(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
تم اختبار كفاءة Phytoseiulus persimilis الافتراسية للسيطرة على Tetranychus urticae خلال الموسم الزراعي 2006- 2007، وذلك ضمن بيت بلاستيكي بمركز اللاذقية لتربية وتطبيقات الأعداء الحيوية، على صنف الفريز Oso grande. أجريت التجربة بمعاملتين، تم متابعة تطور أعداد الفريسة مع الزمن في إحداها، كما تم نشر المفترس في المعاملة الثانية بمعدل 1/10 ( مفترس/ فريسة ) كما تمت متابعة تأثير وجوده في أعداد الفريسة T.urticae. قدّرت كفاءة الافتراس بتطبيق معادلة هندرسون وتلتون كما درست علاقة الارتباط بين المفترس والفريسة. وصل متوسط كفاءة الافتراس إلى أكثر من 82% بعد أربعة أسابيع من إدخال المفترس ثم ارتفعت مع الزمن لتبلغ 100% بعد حوالي ستة أسابيع، سُجّل معامل تضاعف منخفض بالنسبة لكل من T.urticae و. P. persimilis The study was carried out in a greenhouse during 2006-2007, in Lattakia center for rearing natural enemies in order to test the efficacy of Phytoseiulus persimilis in controlling Tetranychus urticae. The experiment included two treatments: the first one to study the development and increasing of prey numbers through time. The second one is to study the effect of the predator on Tetranychus urticae numbers, after releasing the predator in a rate of 1:10 (predator: prey). The efficacy average reached more than 82% after four weeks, and then it reached 100% after six weeks of releasing. Low multiplication was recorded for both T.urticae and P. persimilis.